Pronosticando la inflación mensual en Colombia un paso hacia delante: Una aproximación "de abajo hacia arriba" - Julio César Alonso; Andrés Felipe Rivera (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2017)
– The hierarchical structure of the Colombian Consumer Price Index (CPI) makes possible to calculate inflation as a linear combination of its subcomponents. We use SARIMA models to forecast each component of CPI and construct an forecast of inflation using a lineal combination of the forecasts of these components, i.e. a "bottom to top" approach. In this paper, we asses the out-of-sample performance of the one-step ahead forecast of 12 "bottom to top" methodologies. These methods are compared with an aggregate forecast using a SARIMA model. Our results show that a "bottom to top" method to forecast inflation outperforms an aggregate approach for the case of monthly inflation in Colombia.
Keywords: C32; C53; E31; E37; 330; CPI; inflation; forecasts; "bottom to top"; Colombia